PEMBENTUKAN MORFOLOGI VERBA DALAM BAHASA KOREA - Amy Krisdiana Krisdiana; Rani Jayanti (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2021)
This paper describes the formation of morphological verb in Korean (which is then abbreviated as BK) using the Item of Arrangement (IA) theory. The data has been collected through library research and recording techniques were analyzed according to the process of forming verbs in BK. The result analyses show that the BK verb category is divided into regular verbs and irregular verbs. In Korean morphology (BK), the morphological process that occurs is affixation in the form of suffixes. In Korean morphology (BK), there are suffixes that indicate tense and affirmative polite markers. The components contained in BK are affirmative polite suffix markers, namely –yo or –eoyo and tense marker suffixes. Every root verb in Korean is always followed by a polite marker, namely –yo or –eoyo, while the tense marker sometimes appears between the verb root and the affirmative polite marker –yo or –eoyo. Keywords: morphology, verb, item of arrangement